PENGARUH UMPAN TERHADAP HASIL TANGKAPAN BUBU DASAR DI SUNGAI KAMPAR KANAN DESA SALO KECAMATAN SALO KABUPATEN KAMPAR PROVINSI RIAU - Aprilia Eka Sari; Bustari '; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in May 2016 for 9 days located in Kampar Kanan River in Salo Village, Salo Sub-district, Kampar District, Riau Province. The purpose of this study was to investigate the effect of baits on bottom trap catchment and catch differences with coconut, cassava, rubber seed, and non-feed (as control) feed. In the waters of Kampar Kanan. Then the data collected and analyzed are the catch data in the amount of weight (kg), the type, the length of the fish (cm), the number of weight per species of fish (gr), the number of catch (tail), and environmental parameters. Keyword : fishing ground, environmental parameters, Kampar Kanan river